2017
DOI: 10.2147/ijwh.s125883
|View full text |Cite
|
Sign up to set email alerts
|

Addressing intravaginal practices in women with HIV and at-risk for HIV infection, a mixed methods pilot study

Abstract: Intravaginal practices (IVPs), include intravaginal cleansing (cleansing the inside of the vagina) or intravaginal insertion of products for hygiene, health or sexuality reasons. IVPs are associated with adverse female health outcomes, development of bacterial vaginosis, HIV acquisition and transmission. A mixed methods approach was used in this study to examine the prevalence of IVP, assess reasons for engagement, and perceptions of IVP among a sample of minority (African-American and Hispanic) women infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
2
15
2
Order By: Relevance
“…The girls interviewed indicated having learned about IVPs in both formal and informal settings from peers, mothers, and grandmothers as early as age 10 or 11, soon after the onset of puberty and prior to becoming sexually active. These results are in line with those of previous studies on IVP3,4 which reported that women are introduced to IVPs at an early age by elderly women and use is motivated by male sexual preferences. This finding is also in agreement with Mwenda’s finding which showed that although practices such as IVP may place women at risk for sexually transmitted diseases, these practices are customary in many parts of Africa, culturally driven, and difficult to change 9…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The girls interviewed indicated having learned about IVPs in both formal and informal settings from peers, mothers, and grandmothers as early as age 10 or 11, soon after the onset of puberty and prior to becoming sexually active. These results are in line with those of previous studies on IVP3,4 which reported that women are introduced to IVPs at an early age by elderly women and use is motivated by male sexual preferences. This finding is also in agreement with Mwenda’s finding which showed that although practices such as IVP may place women at risk for sexually transmitted diseases, these practices are customary in many parts of Africa, culturally driven, and difficult to change 9…”
Section: Discussionsupporting
confidence: 92%
“…Data presented in this report are part of a large national qualitative study aimed at exploring vulnerability of adolescent girls and young women to HIV in Zambia. Results from the primary study have been previously published 13,4,5,17. Focus group discussions were held with adolescent and young adult couples in one urban and two peri-urban public health facilities of Lusaka city, Zambia.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations